Moderate Islam as New Identity in Indonesian Foreign Policy: Between Global Role Aspiration and Co-Religious Solidarity - Aryanta Nugraha (JICSA : Journal of Islamic Civilization in Southeast Asian, 2012)
President SBY’s statement that Indonesia is “a country where democracy, Islam and modernity go hand in hand” has underpinned new identity in Indonesia’s foreign policy as a Moderate Islam country. Despite often claim to be the world’s largest community of Muslim, this is the first time Islam in terms of moderate, entered in glossary of Indonesia’s foreign policy as formative factor. While in preivious era Islam was insignificant and played less substantial role in Indonesia’s foreign policy, this paper seeks to scrutinise why is the moderate Islam openly articulated as part of Indonesia’s national identity? What are the purposes of the new foreign policy project in regard to the domestic tension at home and in relations with other Islamic countries and the rest of the world? This paper argues that the democratic moderate Islam identity is important in two ways. First, it is a part of the struggle to mainstreaming the moderate view in the continuing “intra-clash” among the radical and moderate Islam in Indonesia. Secondly, the new identity is put in place to aspire bigger role if not a leadership in international affairs by selling the model of democracy-moderate Islam nexus. The efficacy of this new identity, however will depend on the ability to manage the tension and conflict at home and abroad without fall into blinded coreligionist solidarity interest.